A review study on the seed germination and dormancy of Musa spp. / Noor Farrah Afiqah Mohd Hazani - Mohd Hazani, Noor Farrah Afiqah (Faculty of Plantation and Agrotechnology, 2019)
This review study was related to the production of banana as a commercial fruit in Malaysia by reviewing the seed germination and dormancy of Musa spp. It was carried out in order to review the effects of different treatments of breaking seed dormancy on seed germination rate of Musa spp. The dormancy breaking types that have been studied in this case were mechanical scarification and acid treatment. With mechanical scarification, the seed coats were rubbed using sand paper and others were penetrated with needle on both internal and external integument. For acid treatment, the seeds were immersed into the concentration sulphuric acid (H2SO4) for specific time and then rinsed by using distilled water. Both treatments resulted in successful germination. For mechanical scarification, only small numbers of seeds were infected by contamination like fungi. Others were well germinated. For acid treatment, only seed that had been stored for up to two months germinated. It was found that acid treatment was best applicable for imbibition and breaking seed dormancy for Musa spp.